Analysis of Irrigation Water Use Efficiency in Tungkub Irrigation Area - Darmayasa, Made; Tika, I Wayan; Sucipta, I Nyoman; Sulastri, Ni Nyoman (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Efficiency is one of the methods for determining water management in agricultural land by consider ing the need and availability of irrigation water . The water irrigation use d in Tungkub irrigation area is not supposed to be optimum because of insufficient water management . C onditions of the irrigation area are waste of water and in the dry season there is a shortage of water especially downstream . The purpose of study is to determine efficiency of irrigation water use in the land preparation an d planting phase . To support research, T ungkub I rrigation Area is divided into three areas, area A mostly locat ed upstream, area B mostly in the middle and area C mostly downstream. The research used methods of quantitative analysis by collecting secondary and primary data . Secondary data obtained from Power Nasa, Bali Climatology Station, BMKG region III Denpasar, pekaseh and related officers. Primary data is availability of irrigation water based on water in the channel and observation of the pad dy cultivation process. Results of irrigation water use efficiency in area A when land preparation 59,26%, vegetative ph ase 34,30% and generative phase 20,24%. Area B when land preparation 49,97%, vegetative phase 35,92% and generative phase 73,58%. Area C when land preparation 86,32%, vegetative phase 55,10% and generative phase 35,65%. Water efficiency in areas A, B while soil preparation, all areas while vegetative phase and areas A and C while generative phases are in the category “slightly less”. While land preparation in area C and generative phase in area B are in the "good" category